Stamped Late Roman/Proto-Byzantine amphoras from Halasarna of Kos - Diamanti, Charikleia (Rei Cretariae Romanae Fautorum Acta, 2024)
This paper examines the unique group of stamped local amphoras that was brought to light by the excavation of the University of Athens, at a Late Roman settlement (5th–7th c.) at Halasarna of Kos, in the south-east Aegean Sea. During the systematic study of about 5000 examples of amphoras a large amount was discovered to be of local production.